ANALISIS PENGARUH KREDIT PERBANKAN TERHADAP PERTUMBUHAN EKONOMI - Annisa Salsabila (CV. Denasya Smart Publisher, 2025)
Bank credit is a key financial instrument serving as an intermediary channel to allocate funds to productive sectors. However, its effectiveness in stimulating economic growth varies significantly depending on geographic, temporal, and institutional contexts. This study employs a Systematic Literature Review (SLR) approach using the PRISMA 2020 protocol. A total of 15 qualified articles from accredited national journals published between 2020 and 2024 were analyzed through a rigorous process of identification, screening, eligibility assessment, and data extraction. The findings reveal heterogeneous effects of bank credit on economic growth. Microcredit for SMEs and fintech lending demonstrated significant positive impacts, while investment credit and conventional credit showed mixed outcomes. The effectiveness of credit is influenced by inflation, interest rates, human development index, and technological adoption. Credit transmission mechanisms operate through SMEs, consumption, payment systems, and income distribution. The study highlights the need for adaptive and context-specific policy frameworks. Policymakers are advised to strengthen Islamic banking, support fintech innovation, and develop inclusive regulatory frameworks. Credit policies must consider threshold effects and regional heterogeneity to effectively promote sustainable economic growth